Transforming Connections: A Trauma-Informed and Attachment-Based Program to Promote Sensitive Parenting of Trans and Gender Non-conforming Youth - Dangaltcheva, Antonia; Booth, Chris; Moretti, Marlene M. (Frontiers in Psychology, 2021)
Gender nonconforming and trans youth experience high rates of bullying and victimization, placing them at risk for serious mental health challenges. Parent support is one of the most significant protective factors in this population, and yet few programs are specifically developed to promote parenting sensitivity, understanding, and acceptance. Connect (Moretti, 2020), a trauma-informed and attachment-based group program for caregivers of at-risk adolescents, has been shown to reduce parent stress and depressed mood, increase parents’ sense of efficacy and satisfaction, and reduce parent-teen conflict. Teens benefit from increased attachment security and improved mental health and wellbeing. Treatment effects have been documented to continue for up to two years post-treatment. This paper describes the adaptation of the Connect program to create a new program, Transforming Connections, for caregivers of transgender and gender nonconforming youth. Participants in the first three groups were 20 parents of 16 gender nonconforming youth (ages 12 - 18). Common themes in group discussions related to gender included: coming out, connecting with peers, affirming pronouns/names, medical transition, parental reactions (e.g., confusion, isolation, grief, acceptance), and concerns about safety and mental health. All parents completed the full program, attending on average 9 of 10 sessions. Caregivers reported feeling respected, safe, and welcomed in the program and indicated that learning about attachment enhanced their understanding of their teen and their gender journey as well as themselves as a parent. Additionally, all parents reported applying the ideas discussed in the group frequently (60%) or somewhat frequently (40%). The majority indicated that their relationship with their teen had improved somewhat (65%) or a great deal (20%). Findings provide positive preliminary evidence of the fit and value of Transforming Connections for these families.